Influence of brand equity dimensions on Malaysian consumers’ repurchase intentions for halal store-brand products - Isa, Maryam Ladi (2024)
Consumers often perceive halal store brand products as inexpensive and of inferior quality. This misconception persists, despite the general perception of halal products as safe and affordable due to their halal certification. While, halal certification guarantees adherence to Shariah law throughout the supply chain, instances of violations have eroded consumer trust in halal store-brand products. Given the nascent nature of halal store-brand research in Malaysia, this study investigates the influence of brand equity dimensions on Malaysian consumers repurchase intentions for these products. The equity dimensions included in this study are brand awareness, brand perceived quality, brand loyalty, brand association, brand image, brand perceived value, brand trust, brand price, brand satisfaction, perceived behavioural control, attitude and subjective norms. The specific objectives are: to identify the brand equity dimensions that influence Malaysian consumers repurchase intentions for halal storebrand products; to determine which brand equity dimensions have the most significant influence on repurchase intentions; to evaluate the mediating effect of halal store brand association on halal store-brand image, perceived value, trust, price and satisfaction and to assess the repurchase intention levels of Malaysian consumers for halal store-brand products and evaluate the influence of attitude, subjective norms, and perceived behavioral control in shaping these intentions. Employing the Consumer- Based Brand Equity (CBBE) Theory and the Theory of Planned Behaviour (TPB), a quantitative research design was adopted. Data were collected from 440 respondents in the Klang Valley, Selangor, Malaysia, using an online questionnaire. Structural Equation Modelling (PLS-SEM) was used for data analysis. The key findings show halal store-brand awareness, perceived quality, loyalty, perceived behavioural control, and attitude have significant positive influence on consumers repurchase intention of halal store-brand products. Results show halal store-brand awareness is the most influential equity dimension, halal store-brand association mediates the influence of halal store-brand image, perceived value, and satisfaction on repurchase intention and majority of consumers have a high intention to repurchase halal store-brand products. Practically, the audience for this study includes retailers, marketers (such as hypermarket and supermarket owners) brand managers, who focused on halal products, and branding. Specifically, to those involved in Islamic consumer markets, halal brand management, and retail strategy development. Marketers should capitalize on consumers positive associations to strengthen brand image, perceived value, satisfaction, foster consumers positive attitude towards halal store-brands in their marketing strategies to increase repurchase rates. The findings indicate a strong level of loyalty among consumers towards halal store-brand products. Marketers should leverage on this loyalty by implementing strategies to retain existing consumers and attract new ones by offering incentives, promotions, and rewards for repeat purchases. Social influence plays a significant role in driving purchasing decisions. Therefore, marketers should focus on building strong social networks through positive word-ofmouth to enhance brand awareness and acceptance within the community to strengthen brand image through authenticity and quality. Prioritize transparency and traceability and halal certification to build consumer trust. Offer competitive pricing and valueadded benefits. Educate consumers about product benefits, emphasize social responsibility to enhance brand reputation and trust among consumers. This study offers valuable insights for businesses seeking to navigate the complexities of consumer behaviour and brand relationships. Therefore, understanding the drivers of consumer behaviour and brand relationships, businesses can develop targeted marketing strategies that resonate with Malaysian consumers values, preferences, and cultural sensibilities.